Ostensive Expression On Covid-19 News In The Jakarta Post - Rahim, Rafika (Jurnal Ilmiah Mahasiswa Pendidikan [JIMEDU], 2021)
This research was aimed at investigate: (1) the types of deixis used in Covid-19 in The Jakarta Post online-articles; (2) the types of references used by the deixis found in Covid-19 news in The Jakarta Post online-articles. This research was conducted by using descriptive qualitative method. The data of this research were the sentences in Covid-19 articles which contained deixis. The data were analyzed by using Miles and Hubermans theory which consisted of data reduction, data display and drawing conclusion. The result of this research showed that: (1) there were five types of deixis used in The Jakarta Post online-articles about Covid-19 news. They were person deixis, time deixis, place deixis, discourse deixis and social deixis; (2) there were two types of references used by the deixis found in Covid-19 news of The Jakarta Post news, namely: anaphoric and cataphoric references.